Pengaruh Pemungutan Pajak Reklame Terhadap Penerimaan Pajak Daerah Kota Bandung (Studi Empirik Pada Dinas Pendapatan Daerah Kota Bandung) - Sri Watini; Ita Salsalina Lingga (Universitas Kristen Maranatha, 2010)
The objective of this research is to determine the impact of advertisement tax collection towards regional tax revenue. Survey method is applied with data collected from DISPENDA at Bandung City from year 2005 until 2009 and simple regression analysis is applied in data processing.The research shown that in confidence level of 95%, advertisement tax collection has no significant impact towards regional tax revenue and the correlation between advertisement tax and regional tax revenue is very weak. Keywords: advertisement tax, regional tax revenue